Money Supply, Banking and Economic Growth - Ahmad, Moid (2024)
The primary objective of the research is to understand the interactions between money supply, banking and economic growth for effective policy interventions and business decisions. Based on annual data for the time period (2004-2021), descriptive analysis, correlations, causality tests and panel data regressions are analyzed for a sample from India, Saudi Arabia and UAE to draw conclusions. The results favored the intermediation theory and were contrary to the credit creation theory of banking. It was observed that the GDP of a country can be efficiently explained by financial soundness, broad money, loans and deposits for a country. Also, that the GDP of a country influences banking loans and deposits but not vice versa. The monetary policy of the sample was questioned by the finding that GDP causes banking loans and banking deposits but not vice versa. This important finding will add to the effectiveness in business decision making.